2020
DOI: 10.1088/2053-1591/ab7311
|View full text |Cite
|
Sign up to set email alerts
|

Hot deformation behavior and processing map of ultrafine-grained pure zirconium refined by compounding

Abstract: An ultrafine-grained (UFG) pure zirconium(Zr) refined by compounding with a size of Φ4×6 mm was subjected to a unidirectional compression test using a Gellble-3800 thermal simulation tester at the temperature of 300°C-450°C and a strain rate range of 0.001-0.05 s −1 . Experimental results showed that the flow stress of UFG pure Zr refined by compounding is highly sensitive to temperature and strain rate, and the peak stress decreases with increase in deformation temperature and increases with increase in str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…By comparing the effect of heat treatment on the microstructure and thermal stability of UFG pure copper specimens with those annealed after cold rolling, Molodova et al [28] found that the thermal stability of UFG pure copper prepared by the ECAP process was poor. In addition, Han et al [29] studied the effect of strain rate and temperature on a unidirectional compression test of UFG Zr and revealed that deformation mechanism at higher deformation temperature and lower strain rate may be related to the dynamic recovery and dynamic recrystallization. However, the above-mentioned method is limited to traditional tension and compression deformation.…”
Section: Introductionmentioning
confidence: 99%
“…By comparing the effect of heat treatment on the microstructure and thermal stability of UFG pure copper specimens with those annealed after cold rolling, Molodova et al [28] found that the thermal stability of UFG pure copper prepared by the ECAP process was poor. In addition, Han et al [29] studied the effect of strain rate and temperature on a unidirectional compression test of UFG Zr and revealed that deformation mechanism at higher deformation temperature and lower strain rate may be related to the dynamic recovery and dynamic recrystallization. However, the above-mentioned method is limited to traditional tension and compression deformation.…”
Section: Introductionmentioning
confidence: 99%